Mutations in TAX1BP3 Cause Dilated Cardiomyopathy with Septo‐Optic Dysplasia. Issue 4 (16th March 2015) - Reinstein, Eyal; Orvin, Katia; Tayeb‐Fligelman, Einav; Stiebel‐Kalish, Hadas; Tzur, Shay; Pimienta, Allen L.; Bazak, Lily; Bengal, Tuvia; Cohen, Lior; Gaton, Dan D.; Bormans, Concetta; Landau, Meytal; et al.
<x xml:space="preserve">Abstract</x> The term hereditary cardiomyopathy has been applied to heritable forms of heart failure with identifiable inheritance patterns. Although many cardiomyopathies have a genetic basis, only a limited number of genes have been identified as disease loci. We describe a novel cardiomyopathy syndrome caused by mutations in TAX1BP3; a gene previously not connected to monogenic disorders, thus expanding the spectrum of hereditary cardiomyopathies and suggests that TAX1BP3 is essential for heart development. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>